A STUDY ON THE PROBLEMS FACED BY KADALI CULTIVATORS IN MATTATHUR PANCHAYATH, THRISSUR - V, BINDU.; JOTHI, Dr. K.; S.M, CHANDANRAJ S.M; Joseph, ALDRIN (International Journal of Psychosocial Rehabilitation, 2020)
Kadali is a small and sweet fruited variety of banana which is mainly grown for offerings in temple and is known names like Ambalakadali, Nivedyakadali etc. Around 4000 to 25,000 Kadali Bananas are needed in Guruvayur temple based on the season. It provides employment and income to the common people. It also generated the rare variety of ‘Pooja kadali‘banana which is facing extinction would be rejuvenated. In Mattathoor panchayat alone, 504.85 acres are being cultivated under Kudumbashree’s collective farming and Samagra projects. The major finding is, the project makes the women empowerment to earn for their livelihood. The society gives bonus, so it attracts the common people to cultivate kadali. It’s really benefits the common people and they dedicated their life totally to plant kadali and they feel that Lord Krishna gives blessings their life and believe it will make progress in their lifetime. While comparing with other plantains cultivation of kadali banana is more profitable. But the major problems faced by the cultivators relating to production are pest attacks, Natural calamities and Severe diseases.